Three-Year Follow-Up of Posterior Corneal Elevation in Thin Corneas After Small Incision Lenticule Extraction - Zhao, Yu; Fu, Dan; Chen, Zhuoyi; Zhou, Xingtao (Frontiers in Medicine, 2022)
Purpose To evaluate the changes in posterior corneal elevation in thin corneas after small incision lenticule extraction (SMILE). Methods In this prospective study, 97 eyes of 97 patients undergoing SMILE were recruited. Eyes were categorized into the following groups based on the preoperative minimum central corneal thickness (CCT): group A (37 eyes, 480–499 μm), group B (30 eyes, 500–529 μm), and group C (30 eyes, 530–560 μm). The posterior corneal surface was measured with a Pentacam over a 3-year follow-up period. Changes in the posterior corneal elevation at the central point (PCE), thinnest point (PTE), and predetermined area were measured. Results No iatrogenic keratectasia was observed during the follow-up period. The mean changes in PCE, PTE, and the inferior area in group A were 1.14 ± 3.40 μm, −0.11 ± 3.20 μm, and −0.26 ± 1.23 μm, respectively (P ≥ 0.125). Although statistically significant change in the central-4 mm area was noted, the value was quite small (0.98 ± 1.67 μm) and was not higher than that in the other two groups (P = 0.003). For all three groups, the elevation remained stable or showed a backward change in the central annulus, while there was a small forward displacement in the 6-mm optical zone. In group A, changes in elevation values yielded negative statistical correlations with residual bed thickness and CCT (P ≤ 0.006) (except for the inferior area, the 4-mm and 6-mm optical zone). Conclusions With a strict preoperative assessment, SMILE achieved good safety and efficacy in correcting myopia in thin corneas and enabled a stable posterior corneal surface over a 3-year follow-up period. Synopsis Careful preoperative assessment and suitable surgical design should be taken to ensure posterior corneal stability after SMILE in thin corneas.